Effect of enzyme, multivitamin and growth promoter on growth performance and hemato-biochemical parameters in broiler chicken - Das, MR; Sarker, MMH; Rashid, MB; Miah, MA (International Journal of Natural Sciences, 2016)
To investigate the effect of exogenous enzymes, multivitamin and growth promoter on growth performance and different hemato-biochemical parameters of broilers, ten days old Cobb 500 chicks were used and randomly divided into five equal groups (n=10). Group A was considered as control, fed only with commercial ration. Group B, C, D and E were supplemented with enzymes, multivitamin and enzymes plus multivitamin and growth promoter, respectively for the period of 21 days. Results revealed that body weight was increased significantly (p <0.05) in all four treated groups and highest body weight was recorded in group D. Weights of different organs except viscera (liver, spleen, skin, legs, breast meat, leg meat and viscera) were also varied significantly (p <0.05) among the treated groups. TEC increased significantly (p<0.05) in birds of all treated groups except group E whereas Hb concentration increased significantly (p<0.05) in all treated groups (B, C, D and E) as compared to control group A. Highest PCV was also recorded in group C but all the values were more or less similar and statistically insignificant (p>0.05). Biochemical parameters like AST were decreased significantly (p<0.05) in treated groups except group B and C. But, ALT values decreased significantly (p<0.05) in all treated groups in comparison to control group. It is concluded that combined supplementation of enzyme and multivitamin improved better in body weight and different organs weight gain and improves hemato-biochemical profile in broilers. International Journal of Natural Sciences (2014), 4(1) 1-4